Okotoks: From Trading Post to Suburb - Thomas, Lewis (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1979)
In spite of a growing interest in urban history, Canadian scholars have paid little attention to small towns. In this article a small town in southern Alberta is examined during the years 1890-1950, with particular attention paid to the decade of the 1920s. The author argues that a closer examination of such small centres might throw new light on the complex patterns of Canadian development. Small towns like Okotoks provided a means whereby the first generation of Alberta settlers, predominantly English-speaking, Protestant and British oriented, asserted their peculiar values in the life of the province in spite of the arrival after 1896 of new waves of settlers from the United States and continental Europe.